Eagle Syndrome - Gök, Üzeyir; Yıldız, Mücahit (Fırat University, 2004)
Elongated styloid process is one the cause of cranofacial and cervicofacial pain. The incidence of Elongated styloid process in people has been reported to be 4% and 4% of those presenting wiht clinical semtoms. The mineralization and calcification of styloid complex is seen in 2-4% of general puplic. Eagle syndrome is seen more in women than men between 20 and 40 years of age. Five cases of elongated stiloid proces admidted to our clinic were operated and presented in view of the current literature. ©2004, Fırat Üniversitesi, Tıp Fakültesi

Elonge stiloid proçes kraniofasiyal ve servikofasiyal bölgedeki çok sayıdaki ağrı nedenlerinden biridir. Elonge stiloid proçesin toplumdaki insidan %4 olarak belirtilmiş ve bunlarında %4 ünün semptomatik olduğu rapor edilmiştir. Stilohyoid kompleksin mineralizasyonu ve kalsifikasyonu genel populasyonda %2-4 oranında görülmektedir. Eagle sendromu kadınlarda erkeklere göre daha fazla görülür ve 20-40 yaşları arasında görülme insidansını artar. Tedavisinde ekstenal veya intraoral yaklaşım ile uzun stiloid proçesler kısaltılır. Kliniğimizde intraoral yaklaşım ile opere ettiğimiz 5 vaka literatüre bilgisi ışığında sunulmuştur. ©2004, Fırat Üniversitesi, Tıp Fakültesi
Eagle Sendromu